Serine protease inhibitor 6 protects alloreactive T cells from Granzyme B-mediated mitochondrial damage without affecting graft-versus-tumor effect. (4th March 2018) - Du, Wei; Mohammadpour, Hemn; O'Neill, Rachel E.; Kumar, Sandeep; Chen, Chuan; Qiu, Michelle; Mei, Lin; Qiu, Jingxin; McCarthy, Philip L.; Lee, Kelvin P.; Cao, Xuefang
ABSTRACT: Allogeneic hematopoietic cell transplantation (allo-HCT) is a potentially curative therapy for hematologic malignancies. Donor T cells are able to eliminate residual tumor cells after allo-HCT, producing the beneficial graft-versus-tumor (GVT) effect, but can also cause graft-versus-host disease (GVHD) when attacking host normal tissues. We previously reported that granzyme B (GzmB) is involved in activation-induced cell death (AICD) of donor T cells and exerts differential impacts on GVHD and GVT effect. Serine protease inhibitor 6 (Spi6) is the sole endogenous inhibitor of GzmB that can protect immune and tissue cells against GzmB-mediated damage. This study is aimed to delineate the mechanism by which the GzmB-Spi6 axis regulates allogeneic T cell response. Using multiple clinically relevant murine allo-HCT models, we have found that Spi6 is concentrated in mitochondria during allogeneic T cell activation, while Spi6 −/− T cells exhibit abnormal mitochondrial membrane potential, mass, reactive oxygen species (ROS) production and increased GzmB-dependent AICD mainly in the form of fratricide. Compared with WT T cells, Spi6 −/− T cells exhibit decreased expansion in the host and cause significantly reduced GVHD. Notably, however, Spi6 −/− T cells demonstrate the same level of GVT activity as WT T cells, which were confirmed by two independent tumor models. In summary, our findings demonstrate that Spi6 plays a novel and critical role in maintaining the integrity of T cell mitochondrial function during allogeneic response, and suggest that disabling Spi6 in donor T cells may represent a novel strategy that can alleviate GVHD without sacrificing the beneficial GVT effect.